A review on transition metal oxides in catalysis - Sahoo, Sanjubala; Wickramathilaka, Kaveendra Y.; Njeri, Elsa; Silva, Dilshan; Suib, Steven L. (Frontiers in Chemistry, 2024)
Transition Metal Oxides (TMOs) have drawn significant attention due to their diverse range of properties and applications. The partially filled d orbitals of the transition metal ions, with highly electronegative oxygen atoms, give rise to unique electronic structures that lead to multiple applications due to their magnetic, optical, and structural properties. These properties have a direct influence on chemical reactions that enable tailoring materials for specific applications in catalysis, such as electrocatalysis and photocatalysis. While the potential of TMOs is promising, their development for enhanced functional properties poses numerous challenges. Among these challenges, identifying the appropriate synthesis processes and employing optimal characterization techniques are crucial. In this comprehensive review, an overview of recent trends and challenges in the synthesis and characterization of highly functional TMOs as well as ceramics will be covered with emphasis on catalytic applications. Mesoporous materials play a key role in augmenting their functionality for various applications and will be covered. Ab-initio modeling aspects for the design and development of novel TMO will be also discussed.